AN X-RAY RIETVELD, INFRARED, AND MOSSBAUER SPECTRAL STUDY OF THE NAMN(FE1-XINX)2(PO4)3 ALLUAUDITE-TYPE SOLID SOLUTION - Hatert F.; Hermann R.P.; Long G.J.; Fransolet A.M.; Grandjean F. (My University, 2003)
Several compounds of the NaMn(Fe1-xInx)2(PO4)3 solid solution were synthesized by solid state reaction in air; pure alluaudite-like compounds were obtained for x = 0.00 to 1.00. X-ray Rietveld refinements indicate the presence of Na+ at the At and AT sites, Mn2+ at the MI site, and Fe2+, Fe3+, and In` at the M2 site. The presence of small amounts of In3+ at the M1 site, and Mn2+ at the M2 site, indicates a partially disordered distribution between these cations. A good correlation was also established between the MI-M2 bond distance and the Beta angle of the alluaudite-like compounds. The disordered distribution of Fe2+, Fe3+, and In3+ at the M2 site is confirmed by the broadness of the infrared absorption bands. The Mossbauer spectra, measured between 90 and 295 K, were analyzed in terms of a model that takes into account the next-nearest neighbor interactions around the M2 crystallographic site. In all cases these spectra reveal the unexpected presence of small amounts of Fe2+ at the M2 site, an amount that decreases as the In3+ content increases. The Fe2+ and Fe3+ isomer shifts are typical of the alluaudite structure and vary with temperature, as expected from a second-order Doppler shift. The derived iron vibrating masses and Mossbauer lattice temperatures are within the expected range of values for iron cations in an octahedral environment. The Fe2+ and Fe3+ quadrupole splittings are also typical of the alluaudite structure and the temperature dependence of the Fe2+ quadrupole splitting was fit with the model of Ingalls (1964), which yielded a ground state orbital splitting of ca. 380 to 570 cm-1 for the Fe2+ sites.
Keywords: X RAYS; INFRARED RADIATION; STUDIES; MINERALOGY